A Probabilistic Topic Model on Energy and Transportation Sustainability Perceptions Within Spanish University Students. - Pomeda, J. Rodríguez; Bayas Aldaz, Ceci E.; Sandoval Hamón, L.A.; Sánchez Fernández, F.; Fernández de Navarrete, F. Casani (European Journal of Sustainable Development, 2016)
Universities gather different social groups with diverse perceptions about sustainability issues. Higher Education institutions are interesting organizations to observe emergent social trends related to environment. The behavior (inside and outside the university) of those university stakeholders is related to their perceptions about universities’ policies and procedures on sustainability. We focus our research on the students’ perceptions on sustainability because of the actual and future role of students within the society. With 25 interviews (about 55,000 words), we elaborate a probabilistic topic model about the perceptions of a sample of Spanish university students on energy and transportation sustainability referred to their daily activities in the campuses. Students deal with questions about renewable energy, energy efficiency, recycled materials, or bicycle use. The method allows to obtain the main topics underlying the expressed students’ perceptions. Corpus’ analysis also shows some gaps between students’ perceptions and behaviors. Conclusions are relevant not only to know more on students’ perceptions about sustainability, but to recommend policies to universities and other organizations. Keywords: Education, Students, Perceptions, Energy sustainability, Transport sustainability, Probabilistic topic models.